Chapter 7: Linking commercial bank lending into determinants of price level in Malaysia - Tang, T.C. (Praeger - Greenwood Publishing Group, 2004)
Top financial scholars from around the world analyze regional economic issues in light of the recent Asian financial crisis. As a result of that crisis, and the ensuing reforms, corporations, governments, individual investors have pursued a variety of strategies to cope with the fast-changing economic situation. Each chapter treats a separate issue and offers policy recommendations. Among the theoretical and empirical analyses collected here are those relating to nonperforming loans, economic restructuring, bank forecasting, prediction of corporate failure, Islamic banking issues, new measurem.